Dermatitis Artefacta : A Rare Case of Psychodermatological Disorder - Sanker Roy Biswas, Rajat; Nasir Uddin, Mohammod; Imam, Hasan; Binte Mannan, Shamshunahar (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Dermatitis Artefacta (DA) or Factitious Dermatitis (FD) is a self-inflicted dermatological condition. It is more common in female. It has an underlying motive to assume a sick role for a secondary benefit. This act of deliberate self harm is to reduce the hidden sufferings of emotional distress. Due to polymorphism of the lesions and strong denial of the self-infliction of the injury there is always a diagnostic dilemma. Here we report an interesting case of DA with a confusing presentations where diverse and innovative means for self-inflicting injuries were produced. But initially it is difficult to diagnose the skin lesions, if proper history is not taken providing enough time and lack of proper examination of the lesion further add the difficulties. Case Presentation: Miss Y, 15 years old female, hailing from a nearby Upzilla of Chattogram, got herself admitted 10th July 2023 at Chattagram Maa-O-Shishu Hospital with the complaints of multiple skin eruption with bleeding from the lesions in both arms and lower limbs for three months. The lesions were bizarre, with a tapering end at various stages of healing, and were not compatible with any known dermatological disorder. Her mini mental state examination was normal and she had no delusions or hallucinations. Conclusion: Lack of proper identification of the underlying psychiatric disturbances may be the major cause of treatment failure and loss of follow up. Key words: Dermatitis artefacta; Dermatologist; Factitious dermatitis; Polymorphism; Psychiatry. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 104-107